Foxy and Egg - Smith, Alex T. (Holiday House, 2011)
Delightful hostess Foxy DuBois invites Egg over for dinner. While Egg is taking notice of Foxy's chicken-themed art, Foxy is in the kitchen devising her breakfast menu: Egg. Foxy serves an indulgent dinner, she wants a big, delicious Egg. Then they play games, Foxy also wants a fit Egg. At Foxy's insistence, Egg spends the night, "I have something even more wonderful planned for breakfast," Foxy says. But in the morning, Foxy is the one in for a surprise!